Dampak Media Sosial Bagi Perkembangan Kognitif Anak di SMA Negeri 4 Takalar - Wahyu Munandar (ABDI SAMULANG: Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service aims to investigate and provide a deeper understanding of the impact of social media usage on the cognitive development of students at SMA Negeri 4 Takalar, with activities conducted on November 24, 2023. Social media has become a dominant phenomenon in the lives of adolescents, raising questions about the implications of this behavior on their cognitive aspects. A community service approach was employed, involving observations and interviews with students at SMA Negeri 4 Takalar through discussion sessions. The outcomes of this community service highlight that social media usage can have both positive and negative impacts on the cognitive development of children. Positive aspects include increased creativity, expanded insights, and critical thinking abilities. On the other hand, the risks of information overload and a decline in direct social interactions are significant concerns. The roles of parents and educators are identified as crucial in guiding children to wisely manage their use of social media. Awareness of the importance of a balanced approach and appropriate management of social media for children is the essence of this community service effort. Through this activity, it is hoped that SMA Negeri 4 Takalar will gain a better understanding and manage the impact of social media usage on the cognitive development of children. Dissemination of information and empowerment for parents, educators, and students are expected to contribute positively to creating an environment that supports healthy cognitive development for children in this digital era.